Online Sales Cycle Accounting Information System At Elraf Woodcraft Gallery Dusun Telogogede Trowulan Mojokerto (Study Pada Galeri Elraf Woodcraft Mojokerto) - Chakim, Muchamad Ainul; Dewianawati, Dwi; Dian Hastuti, Poppy Meilina (PRAGMATIS, 2024)
This thesis aims to examine the accounting information system that is running at Elraf Woodcraft which is engaged in a craft manufacturing business whose sales are carried out online. The research method used is a qualitative method with an observation approach by observing business activities. The data presented in the form of descriptive narratives that seek to clearly describe events related to accounting information systems in handicraft manufacturing businesses. Data analysis techniques are carried out by means of researcher interpretation of the data obtained and data reduction by drawing conclusions. The results showed that the accounting information system in Elraf Woodcraft manufacturing business has not been a special concern for business owners because all records are done manually by business owners directly and currently the focus of business owners is still on promotion and product development. From the observations made by the author, it can be concluded that the procedures of the cash receipt cycle, cash disbursements, inventory, employee payroll and presentation of financial reports along with forms and documents related to all transactions carried out. In addition, there is a need for a supply / delivery section and a finance section to help sustain business activities so that business owners focus on product promotion and development which in turn will make the business grow even more because business owners are more concentrated on accelerating sales.